Biochemical Screening of Intellectually Disabled Patients: A Stepping Stone to Initiate a Newborn Screening Program in Pakistan - Wasim, Muhammad; Khan, Haq Nawaz; Ayesha, Hina; Goorden, Susanna M. I.; Vaz, Frederic M.; van Karnebeek, Clara D. M.; Awan, Fazli Rabbi (Frontiers in Neurology, 2019)
Inborn errors of metabolism (IEMs) are rare group of genetic disorders comprising of more than 1000 different types. Around 200 of IEMs are potentially treatable through diet, pharmacological and other therapies, if diagnosed earlier in life. IEMs can be diagnosed early through newborn screening (NBS) programs, which are in place in most of the developed countries. However, establishing a NBS in a developing country is a challenging task due to scarcity of disease related data, large population size, poor economy and burden of other common disorders. Since, not enough data are available for the incidence of IEMs in Pakistan; therefore, in this study, we set out to find the incidence of various treatable IEMs in a cohort of intellectually disabled patients suspected for IEMs, which will help us to initiate a NBS program for the most frequent IEMs in Pakistan. Therefore, a total of 429 intellectually disabled (IQ<70) patient samples were collected from Punjab, Pakistan. A subset of 113 patient samples was selected based on the clinical information for the detailed biochemical screening. Advanced analytical techniques like, Amino Acid Analyzer, GC-MS, UHPLC-MS and MS/MS were used to screen for different treatable IEMs like aminoacidopathies, fatty acid β-oxidation disorders and mucopolysaccharidoses (MPS) etc. A total of 14 patients were diagnosed with an IEM i.e. 9 with homocystinuria, 2 with MPS, 2 with Guanidinoacetate methyltransferase (GAMT) deficiency and 1 with sitosterolemia. These IEMs are found frequent in the collected patient samples from Punjab, Pakistan. Thus, present study can help to take an initiative step to start a NBS program in Pakistan, especially for the homocystinuria having highest prevalence among aminoacidopathies in the studied patients, and which is amenable to treatment. This endeavor will pave the way for a healthier life of affected patients and will lessen the burden on their families and society.